Development of poly (1, 8-octanediol citrate)/chitosan blend films for tissue engineering applications - Zeimaran, Ehsan; Pourshahrestani, Sara; Pingguan-Murphy, Belinda; Kong, Daniel; Naveen, Sangeetha Vasudevaraj; Kamarul, Tunku; Kadri, Nahrizul Adib (Elsevier, 2017)
Blends of poly (1, 8-octanediol citrate) (POC) and chitosan (CS) were prepared through solution casting technique. Films with different component fractions (POC/CS: 100/0, 90/10, 80/20, 70/30, 60/40, and 0/100) were successfully prepared and characterized for their mechanical, thermal, structural and morphological properties as well as biocompatibility. The incorporation of CS to POC significantly increased tensile strength and elastic modulus and presented limited influences on pH variation which is important to the biocompatibility of biomaterial implants. The assessment of surface topography indicated that blending could enhance and control the surface roughness of the pure films. POC/CS blends well-supported human dermal fibroblast cells attachment and proliferation, and thus can be used for a range of tissue engineering applications.